The Realization of Thematic Progression in the Essays of English Undergraduate Students - Maharani Robiatul Islam; Dwi Rukmini; Sri Wuli Fitriati (English Education Journal, 2022)
This study focuses on the realization of thematic progression, the problems concerning the thematic progression, and the coherence of English undergraduate students’ essays in one of the private universities in Lubuklinggau. The researchers investigated en argumentative essays written by the third-semester students by employing descriptive qualitative with written discourse analysis. The researchers used documentation and interview as the instruments. This study used Eggins’ theory (2004). This study revealed that the students mainly realized the thematic progression patterns in their writing, although they did not have a proper thematic progression insight. The students applied Theme reiteration, zig-zag pattern, multiple-Rheme pattern, and split Theme in the thematic progression. Meanwhile, the problems concerning the thematic progression were the problem of brand-new Theme, empty Rheme, incomplete clause, and confusing selection of textual Theme. Brand-new Theme mainly occurred in students’ essays, in which they carried forward the new information that did not relate to the preceding clause. Ten students’ argumentative essays were more coherent in terms of coherence as they had already employed various thematic progression patterns and were not monotonous in one pattern only. To sum up, although theoretically, they lack an understanding of thematic progression, they have practically applied the various thematic progression patterns and made their essays more coherent.